Python and R codes for "Exploring the role of parental proximity in the maternal-neonate bond and parental investment in moose (Alces alces) through post-capture movement dynamics" ... - DelGuidice, Glenn; Ahmadkhani, Mohsen; St-Louis, Veronique; Severud, William; Obermoller, Tyler (Data Repository for the University of Minnesota, 2020)
The submitted python script performs moose movement analyses (i.e dynamic interaction (DI) values, and reunion analysis). The R script measures MCP and KDE home range values for the animals. ...